Vaccination ecosystem health check: achieving impact today and sustainability for tomorrow. Issue 2 (January 2017) - Saadatian-Elahi, Mitra; Bloom, David; Plotkin, Stanley; Picot, Valentina; Louis, Jacques; Watson, Michael
Abstract Background Vaccination is a complex ecosystem with several components that interact with one another and with the environment. Today's vaccine ecosystem is defined by the pursuit of polio eradication, the drive to get as many of the new vaccines to as many people as possible and the research and development against immunologically challenging diseases. Despite these successes, vaccine ecosystem is facing keys issues with regard to supply/distribution and cost/profitability asymmetry that risk slowing its global growth. The conference "Vaccination ecosystem health check: achieving impact today and sustainability for tomorrow" held in Annecy-France (January 19–21, 2015) took stock of the health of today's vaccination ecosystem and its ability to reliably and sustainably supply high-quality vaccines while investing in tomorrow's needed innovation. Main findings Small and decreasing numbers of suppliers/manufacturing facilities; paucity of research-driven companies; regulatory pressures; market uncertainties; political prioritization; anti-vaccine movements/complacency; and technological and programmatic issues were acknowledged as the major challenges that could weaken today's vaccination ecosystem. The expert panel discussed also drivers and barriers to a sustainable vaccination ecosystem; the metrics of a vaccination ecosystem; and what should be added, removed, increased, or reduced to maintain the health of the vaccination ecosystem.